Improving Student’s Higher Order Thinking Skills (HOTS) through Jigsaw - Emy Sudarwati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
This Classroom Action Research aims to improve students’ HOTS (High Order Thinking Skills) through the application of jigsaw. This study was based on a model proposed by Elliott and was implemented for three cycles. The subjects were 15 students of the third semester students of English department taking Academic Reading course.The data collection instruments include observation, test, and documentation. The data were obtained from pre and post-test of each cycle. The findings revealed that jigsaw learning models could increase students’ HOTS (High Order Thinking Skills). Jigsaw is able to boost students participation into an active learning and it can also improve student’s HOTS (High Order Thinking Skills) as jigsaw itself will be followed by other activities like asking questions, discussing in groups, analyzing the results and providing feedback.